Material para construção civil a partir de lodo de estação de tratamento de água, lama de polimento de mármore e resíduo de produção de cal - Hackbart, Fernanda Meireles (2015)
The rapid population growth is the great motivator for the development of the construction industry and the increased demand for drinking water, resulting in a gradual increase in the generation of solid waste. Thus, this work was carried out in order to recycle industrial and municipal wastes incorporating them into materials for civil construction. The composite produced from water treatment sludge and marble polishing mud, applying lime production waste as a binder, was evaluated for its mechanical performance and its morphological structure. The raw materials were characterized for their chemical composition, mineralogy, morphology, particle size and also the moisture content. With the featured materials nine compositions have been developed varying the content of the water treatment sludge between 25 to 50%, marble polishing mud between 35 to 50% and the lime production waste between 10 to 30%. The composites were subjected to mechanical strength tests, water absorption, chemical and mineralogical composition and morphology. The developed materials presented, on the 3rd day of hydration, maximum strength value of 4.65 MPa, the 7th day 6.36 MPa, on the 14th day 6.74 MPa, the 28th day 5.98 MPa, on the 60th day 8.52 MPa at 90th day 11.75 MPa and 180th day 12.06 MPa. The water absorption values after 28 days of hydration ranged from 16.27% to 26.32% and after 90 days, from 13.57% to 23.56%.